História, Tecnologias Digitais e Mobile Learning: ensinar História na era digital - Joaquim Ramos de Carvalho (Investigação, 2019)
The book "History, Digital Technologies and Mobile Learning: Teaching History in the Digital Age" presents us with a set of reflections about the relationship between History, Education and Technologies, with particular attention to teaching History through mobile technologies. These are current, important and necessary reflections, especially when we consider the conditions we have experienced in the context of digital culture. Based on a theoretical-experimental study, the friends and researchers Sara Dias-Trindade and Joaquim Carvalho offer us an exquisite critical-reflexive and propositive analysis on some possibilities of incorporating digital information and communication technologies in the teaching-learning process in the area of Story. It is the coroation of an intense work and commitment of the authors to contribute as much to the area of Education and Technologies as to its base area: History. Certainly, with this fruit of their efforts, the scientific and educational community gained a lot. [Daniel Mill]